The Playing Of Vasilli Svietlovidoff's Character In Anton P. Chekhov's Swan Song Translation Of Djohan A Nasution With Method Of Acting The Stanislavski System - Lubis, Abdul Haris; Susanti, Desi; Alamo, Enrico (Creativity And Research Theatre Journal, 2023)
Playing the character Vasilli Svietlovidoff in the script "Nyanyian Angsa" by Anton P. Chekhov, translated by Djohan A Nasution, is an effort to bring the character to life for performance. The formulation presented in this context is how to analyze the character of Vasilli Svietlovidoff and how to portray the character using Stanislavski's The System method. This conceptual framework employs a representational approach to realize a performance in a realistic style. The correlation between realism and The System method accommodates the actor to bring the character Vasilli Svietlovidoff to life realistically.